Penerapan Algoritma Bayes Terhadap Pengguna Sosial Media yang Ketergantungan - Matondang, Zekson Arizona; Rezel Purba, Doni El (Jurnal Teknik Informatika UNIKA Santo Thomas, 2021)
The Bayes method is a method for generating parameter estimates by combining information from the sample and other previously available information. The Bayes approach to statistical estimation methods combines the information contained in the sample with other previously available information. The Bayesian technique uses the initial distribution together with the evidence contained by the sample to calculate the posterior distribution for the parameter . Conclusions regarding the next parameter are based on the posterior distribution and the parameters in this sample are social media dependent parameters